Ar Lietuvos Respublikos Konstitucinio Teismo jurisprudencijos kontekste lis pendens turėtų būti konstituciniu principu? - Šekštelo, Albertas (Vilnius University Open Series, 2024)
The Constitutional Court of Lithuania is the watchdog of the Constitution which has been forming its official constitutional doctrine for over thirty years and has decided on many important legal issues. However, at least at the Constitutional Court’s level, it is still to be discussed whether lis pendens should be treated as the constitutional principle. It is widely accepted that it is undesirable to have a situation where parallel proceedings involving the same parties and the same cause of action are continuing in different countries simultaneously. When there is at least one final court decision on the merits, the res iudicata principle engages and prevents the possibility of a concurring decision. It is also recognized on the international level and at the level of the Constitutional Court of Lithuania that the res iudicata principle is, respectively, universal and constitutional. However, before the res iudiata protection steps in, lis pendens should prevent the parallel proceedings. This article argues whether lis pendens and res iudicata are, in principle, the two sides of the same coin and, if so, whether lis pendens, along with res iudicata, could have the status of a constitutional principle.